Analysis of Inserted Transformer Installation to Reduce Distribution Transformer Overload at PT PLN (Persero) ULP Abepura, Koya Barat - Dultudes Mangopo; Ekawati Margaretha Ohee; Idham Khaliq (Manunggal Halim Jaya, 2026)
The continuous increase in electrical energy demand, particularly in semi-urban areas, has created significant challenges for the reliability and operational performance of power distribution systems. One critical problem is the occurrence of overload conditions on distribution transformers, which may accelerate insulation degradation, increase thermal stress, and reduce equipment lifespan. This study aims to evaluate the effectiveness of installing an inserted transformer as a technical solution to mitigate overload in the medium-voltage distribution network of PT PLN (Persero) ULP Abepura, Koya Barat. A descriptive quantitative case study approach was employed using field measurement data from the ABE-262 distribution transformer before and after the installation of a 160 kVA inserted transformer. The measured parameters included phase current, voltage profile, transformer loading percentage, phase imbalance, and neutral current during peak load time (WBP) and off-peak load time (LWBP). The results show that the loading of the main transformer decreased from 92.40% to 63.12% during WBP and from 78.94% to 26.56% during LWBP. Meanwhile, the inserted transformer absorbed only 13.32% of the total load during WBP and 9.47% during LWBP, indicating the availability of reserve capacity for future demand growth. The installation also improved phase balance, as shown by the reduction in phase imbalance from 12.4% to 5.6%, and reduced neutral current from 69.7 A to 49.3 A during LWBP. These findings confirm that the inserted transformer is an effective, economical, and practical solution for reducing transformer overload, improving load distribution, and enhancing distribution system reliability. In addition, this strategy provides operational redundancy and reserve capacity, thereby supporting the long-term resilience of distribution networks in areas with limited infrastructure.